The insights and gains achieved by the fusion of two concepts: Disorder and complexity theory. - Thomson, Wendy (British Journal of Healthcare and Medical Research, 2022)
The aim of this manuscript is to put forward the justification and efficacy value of the unification of both the adjective disorder and the science of complex adaptive systems (CAS) as a new recognised science of disorder. Why? Because arguably there has never been a time when it is as imperative to understand the dynamics master disorder as it is currently. At a time when rapid change and the consequential disorder is occurring in every sphere of life. When globally mankind was unprepared for the covid pandemic. The Covid 19 virus might be extremely minuscule - 17 nanometre wide, but few would now doubt its power and capability to cause rampant disorder. Catching nations unprepared, causing insecurity, the sudden threat of death, and the inability to predict, or to prevent this new virus throwing the world into global chaos. The global disorder was and still is influencing all spheres of life: biopsychosocial – medically: environmentally, politically, and economically. However, the very nature of any disorder is that it is ubiquitous, it possesses inherent characteristics which cause a ripple effect; it is impossible to put it back in the box. The word "disorder" in this article is intended to cover all disorder and not to be restricted or identified with just one area of concern, e.g., a disorder caused by acts of terrorism or medical disorders etc. The very nature of disorder is that it can and often does occur suddenly it is unforeseen. The consequences have the potential to generate unconsidered reflexive, alarmist reactions. Reactions with hindsight which may impede the preferred logistical coping strategies. Any response to disorder whether it be microbes, or on the macro level such as war are naturally dependent on the scale, magnitude, impact, and then the resources necessary to restore or attempt order as previously mentioned. This article questions whether the prevailing arena must be and makes an argument for the need for a scientific approach – a progression from being vulnerable to disorder to being in control of disorder whichever way it is manifested. The recommendation is to see disorder as a whole: a CAS system of disorder with many interacting parts and variables, using all the predictive modelling now available by employing the new science of CAS.